Sedentary behavior and physical activity one year after colorectal cancer diagnosis: results from the ColoCare Study - Viskochil, Richard; Lin, Tengda; Gigić, Biljana; Himbert, Caroline; Bandera, Victoria M.; Skender, Stephanie; Holowatyj, Andreana N.; Schrotz-King, Petra; Steindorf, Karen; Strehli, Ildiko; Mutch, Matthew G.; Chao, Dante; et al. (Journal of cancer survivorship, 2025)
Physical activity plays key roles in colorectal cancer survivorship; however, the impact of different clinicodemographic outcomes on cross-sectional and longitudinal objectively measured physical activity 12 and 24 months post-diagnosis are unclear.
Gesehen am 02.12.2025